Pattern of anxiety, depression, and suicidality among in-school adolescents in Bauchi, North-East Nigeria - Mohammed, Amina; Mohammed, Nazeef; Rasaki, Aliu; Oyedun, Rotimi; Gadzama, Bulus N.; Okoh, Elizabeth O. (International Journal Of Community Medicine And Public Health, 2024)
Background: Adolescence is a crucial period of development resulting in significant changes in physical appearance, and psychological functioning. Globally, mental health disorders account for 16% of the global burden of disease and injury in adolescents. The study aims to provide baseline information on adolescents' mental health in Bauchi State. Methods: A cross-sectional study design was employed in this study. Using systematic sampling technique, 672 in-school adolescents aged 10-19 who gave assent/consent were selected. SPSS was used to analyze the data. Results: The mean age of the respondents was 15±2.0, more respondents had no or minimal depression (65.0). However, 0.7% were moderately severely depressed. Most respondents (88.7%) had minimal anxiety, while 1.5% and 0.3% had moderate and severe anxiety respectively. Almost one-quarter of the respondents (23.2%) had thought of ending their life in the past month before the survey with up to 4.2% attempting suicide. Adolescents from polygamous settings were up to 70% less likely to attempt suicide compared to those in a monogamous setting and this was statistically significant with a p-value of 0.039 and CI (0.167-0.785). Furthermore, those whose parents were not in a marital union were 2.9 times more likely to attempt suicide compared to those whose parents were still in union and living together. This was statistically significant with a p-value of 0.018 and CI (1.203-7.060). Conclusions: Early intervention and a multi-pronged public health approach are crucial to safeguard this vulnerable population's mental well-being to enable them to thrive and reach their full potential.